Exploring Pilgrimage Tourist Typologies in Cikakak Tourism Village - Cahyadi, Hery Sigit; Sumardi, Valentino; Rosadi, Asep; Nurjamal, Daeng (Journal of Tourism Sustainability, 2024)
Cikakak Village, located in Banyumas Regency, Central Java, is a notable pilgrimage tourism destination. The village features the Saka Tunggal Mosque, established in 1222 AD, a pivotal site for spreading Islam in Central Java. Adjacent to the mosque is the Tomb of Kyai Toleh, an influential Islamic figure. This site is particularly significant for Kejawen adherents, who integrate Islamic practices with Hindu traditions. This study identifies the motivations of tourists visiting Cikakak Village, categorizing them into five levels: Nirvana Level, for those seeking spiritual transcendence; Transitional Level, for those praying for safety while still engaged in worldly matters; Worldly Level, for individuals with materialistic goals like career and wealth; Ancestry Pilgrim Tourists, who honour their ancestors on specific days; and Heritage Pilgrim Tourists, who are interested in the mosque’s unique history and architecture. Using a qualitative, descriptive research method, data were collected through interviews with mosque and tomb caretakers and community leaders. Direct interviews with tourists were impossible due to their secretive nature; thus, caretakers provided the necessary insights. The study aims to understand the typologies of pilgrim tourists, offering insights to enhance the services and products provided by the local community to accommodate these visitors better.